Sociology of Debt: States, Credit Markets, and Indebted Citizens. Issue 3 (March 2015) - Kus, Basak
Abstract Within the context of the recent financial crisis, the causes and implications of mounting levels of household indebtedness have begun to be examined from a variety of angles: Why have nations differed so drastically, historically speaking, in terms of the level of debt that their citizens carry? Why have patterns converged over the past few decades, with levels of indebtedness increasing across the board? This paper considers these questions from a sociological perspective. I first consider the role of political, institutional, economic, and cultural factors, as well as individual characteristics, in shaping the demand for and supply of credit and the degree and nature of household indebtedness in and across nations. I then attempt to explain the cross‐national convergence towards rising indebtedness over the past few decades by situating the transformation of these various demand and supply side factors under the neoliberal regime.